2001
DOI: 10.1097/00007890-200102150-00011
|View full text |Cite
|
Sign up to set email alerts
|

REDUCED TRANSFUSION REQUIREMENTS BY RECOMBINANT FACTOR VIIa IN ORTHOTOPIC LIVER TRANSPLANTATION

Abstract: A single dose of 80 microg/kg rFVIIa significantly reduced transfusion requirements during OLT. Further study is needed to establish the optimally effective and safe dose of rFVIIa in orthotopic liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
137
2
5

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(150 citation statements)
references
References 23 publications
6
137
2
5
Order By: Relevance
“…In a small single-center experience we published last February in Intensive Care Medicine, 3 at variance with the first preliminary study published by Hendriks et al, 4 we were not able to find any difference in blood loss and transfusion requirements whether or not the drug was administered. We used rFVIIa (20 /kg at the start of operation plus 20 /kg 30-40 minutes after reperfusion in case of significant bleeding) in 6 patients with end-stage liver disease (Child-Turcotte-Pugh, 9 Ϯ 2.5; range, 9-11) who underwent OLT in February 2003.…”
contrasting
confidence: 68%
See 1 more Smart Citation
“…In a small single-center experience we published last February in Intensive Care Medicine, 3 at variance with the first preliminary study published by Hendriks et al, 4 we were not able to find any difference in blood loss and transfusion requirements whether or not the drug was administered. We used rFVIIa (20 /kg at the start of operation plus 20 /kg 30-40 minutes after reperfusion in case of significant bleeding) in 6 patients with end-stage liver disease (Child-Turcotte-Pugh, 9 Ϯ 2.5; range, 9-11) who underwent OLT in February 2003.…”
contrasting
confidence: 68%
“…Blood loss and transfusion requirements did not statistically differ in the treated group (blood loss, 3,500 Ϯ 1,300 mL; range, 1,600-5,000 mL; packed red cells, 9 Ϯ 4 units; range, 4-11 units) mL and in controls (blood loss, 1,800 Ϯ 1,200 mL; range, 500-4,000 mL; packed red cells, 7 Ϯ 2.5; range, 4-10. 3 On the contrary, according to the data reported by Hendriks et al, 4 we found improvements in the following thromboelastographic parameters: r (reduced, P Ͻ 0.05), alpha angle (increased, P Ͻ 0.05), maximum amplitude (tendency toward larger maximum amplitude, not statistically significant). All the patients were discharged in good conditions and are alive (follow-up 16 months).…”
contrasting
confidence: 39%
“…9 The observed anticoagulant effect of aprotinin is in contrast to effects of recombinant factor VIIa, another prohemostatic drug, recently used in OLT to reduce intraoperative blood loss. 35 Recombinant factor VIIa is a very potent stimulator of the coagulation system, which results in increased generation of thrombin, reflected in vitro by a significant shortening of prothrombin time, APTT, and r on thromboelastography. 36 Aprotinin does not have these effects: it does not stimulate the coagulation cascade and has no intrinsic procoagulant effect.…”
Section: Discussionmentioning
confidence: 99%
“…One study has demonstrated that a single dose of rFVlIa (80 mcg/kg) could reduce transfusion requirements in cirrhotic patients undergoing orthotopic liver transplant [15]. Controlled trials have shown rFVIIa to be of no benefit in reducing transfusion in liver resection or transplantation.…”
Section: Perioperative Blood Lossmentioning
confidence: 99%